Lesson Learned Lee Hsien Loong's Strategic Leadership on Maritime Security at Malacca Strait Choke Point - Faradilla, Auriga Putri; Soemantri, Asep Iwa; Prakoso, Lukman Yudho; Suwarno, Panji; Pulungan, Ahmad Ari Syahputra; Alriandi, Aldy Surya; Inayah, Atikah; Putri, Cintya Yelena (PT FORMOSA CENDEKIA GLOBAL, 2024)
This article explores the lessons learned from Lee Hsien Loong’s strategic leadership in maintaining maritime security in the Straits of Malacca, a vital chokepoint for global traffic. Through an analysis of the strategies implemented, including trilateral collaboration through the Malacca Strait Patrols (MSP), the use of advanced surveillance technology, and strengthening military capacity, the article identifies key measures that contributed to security stability. It also evaluates the relevance of lessons from Singapore’s experience to other maritime regions. The findings suggest that Lee Hsien Loong’s integrated approach can be applied to enhance security in other global chokepoints, offering an effective model for addressing maritime security challenges across contexts.